Two closely related 2-(benzofuran-2-yl)-2-oxoethyl benzoates: structural differences and C 14H...O hydrogen-bonded supramolecular assemblies - Li, Yee Then; C. S. , Chidan Kumar; Huey, Chong Kwong; Win, Yip Foo; Siau, Hui Mah; Ching, Kheng Quah; S., Naveen; Warad, Ismail (International Union of Crystallography, 2017)
The compounds 2-(1-benzofuran-2-yl)-2-oxoethyl 2-nitrobenzoate, C17H11NO6 (I), and 2-(1-benzofuran-2-yl)-2-oxoethyl 2-aminobenzoate, C17H13NO4 (II), were synthesized under mild conditions. Their molecular structures were characterized by both spectroscopic and single-crystal X-ray diffraction analysis. The molecular conformations of both title compounds are generally similar. However, different ortho-substituted moieties at the phenyl ring of the two compounds cause deviations in the torsion angles between the carbonyl group and the attached phenyl ring. In compound (I), the ortho-nitrophenyl ring is twisted away from the adjacent carbonyl group whereas in compound (II), the ortho-aminophenyl ring is almost co-planar with the carbonyl group. In the crystal of compound (I), two C 14H